2007
DOI: 10.1007/s11199-006-9143-7
|View full text |Cite
|
Sign up to set email alerts
|

Love Thyself Before Loving Others? A Qualitative and Quantitative Analysis of Gender Differences in Body Image and Romantic Love

Abstract: The present study was designed to explore the intersection of body esteem, romantic love, and gender through qualitative and quantitative analyses. Male (n= 107) and female (n=113) undergraduates completed the Body Esteem Scale (BES), four Romantic Love Experiences Scale (RLES) subscales, and two open-ended questions about the interrelation between body esteem and relationships. For both genders, significant correlations emerged between the BES and RLES, suggesting a link between body experience and romantic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…10 Research also suggests that, like eating disorders themselves, the eating disorderinterpersonal problem relation is stronger in women than men, 11 and that women with bulimia nervosa tend to experience more interpersonal difficulties than women with anorexia nervosa. 12,13 Brown et al 14 found that, whereas women with binge-eating disorder tend to eat more than others and women with anorexia nervosa tend to eat less than others across social situations, women with bulimia nervosa tend to eat more on average, but less when social cues regarding food intake are elicited, further suggesting an important relation between interpersonal problems and bulimic features.…”
Section: Introductionmentioning
confidence: 99%
“…10 Research also suggests that, like eating disorders themselves, the eating disorderinterpersonal problem relation is stronger in women than men, 11 and that women with bulimia nervosa tend to experience more interpersonal difficulties than women with anorexia nervosa. 12,13 Brown et al 14 found that, whereas women with binge-eating disorder tend to eat more than others and women with anorexia nervosa tend to eat less than others across social situations, women with bulimia nervosa tend to eat more on average, but less when social cues regarding food intake are elicited, further suggesting an important relation between interpersonal problems and bulimic features.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that trust and self-perceived desirability are separate constructs; the former relates to a general expectation of how people will behave while the latter relates to a perception of how attractive one generally appears to opposite-sex others. Nevertheless, whilst we conceive of these variables as being distinct, there is evidence that they covary to some degree (Ambwani & Strauss, 2007;Cash, Theriault, & Annis, 2004). In fact, Ambwani and Strauss (2007) have shown that a combined measure of trust and jealousy may predict body esteem in women.…”
Section: Methodsmentioning
confidence: 81%
“…Nevertheless, whilst we conceive of these variables as being distinct, there is evidence that they covary to some degree (Ambwani & Strauss, 2007;Cash, Theriault, & Annis, 2004). In fact, Ambwani and Strauss (2007) have shown that a combined measure of trust and jealousy may predict body esteem in women.…”
Section: Methodsmentioning
confidence: 81%
“…The BES is internally reliable with an alpha range of .78 to .87 for its subscales (Franzoi and Shields 1984). Similar to other researchers' use of the BES (Ambwani and Strauss 2007;Steinfeldt et al 2011), BES total scores rather than subscale scores were used to define body satisfaction as a general construct. For this study, Cronbach's alpha was .91 for the control group, .92 for the D/NDM group, and .95 for the D/DM group.…”
Section: Body Esteem Scalementioning
confidence: 99%